PENGARUH BRAND IMAGE, KUALITAS PELAYANAN, KUALITAS PRODUK, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus Pada Konsumen Handphone Xiaomi di Alibaba Kota Batu) - Ubadillah Mohsyin; Rois Arifin; Afi Rahmat Slamet (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThis study aims to determine the effect of brand image, service quality, product quality, and price influence simultaneously or partially on purchasing decisions. The data used in this study are primary data, the study population of 192 customers at the Alibaba counter, while the study sample was taken from the population using a sampling technique in the form of a purposive sampling method. The results obtained using multiple linear regression test Y = 10,848 + 0,359 X1 + 0,221 X2 + 1,054X3 + 0,994X4 + e. The results of this study indicate that partially brand image variables, service quality, product quality, and price have a positive influence on purchasing decisions.Keywords: Brand Image, Service Quality, Product Quality, Price and Purchasing Decision